Pengaruh Konseling Humanistik Terhadap Sikap Membully Pada Siswa Kelas XI SMA Negeri 1 Sumbawa Besar - Saskia Tristanty; Wayan Tamba; Jessica Festy Maharani (Masyarakat Cita Insani (YAMACITA) Bergerak Dibidang Penelitian, Pendidikan, Pelatihan, Research, 2026)
This study aims to determine the effect of humanistic counseling on the bullying attitudes of students in class XI IPA 3 at SMA Negeri 1 Sumbawa Besar. Bullying behavior in the school environment remains an issue affecting students' psychological, social, and academic aspects, necessitating a counseling approach capable of fostering individual awareness and responsibility. The study employs a quantitative approach with a pre-experimental, one-group pre-test/post-test design. The sample consisted of 10 students selected via purposive sampling. Data were collected using a bullying attitude questionnaire and analyzed using a t-test. The results show a calculated t-value of 6.443, which exceeds the t-table value of 2.262 at a significance level of 0.05. This indicates that humanistic counseling has a significant effect on reducing students' bullying attitudes. Thus, the humanistic approach can serve as an alternative guidance and counseling service to foster more positive social behavior within the school setting.